2021
DOI: 10.1155/2021/7365204
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Prognostic Value of Leucine‐Rich α2 Glycoprotein 1 in Pediatric Spinal Cord Injury

Abstract: Objective. Leucine-rich α2 glycoprotein 1 (LRG1) is a novel cytokine, which is believed to be involved in the inflammatory process of a series of diseases. However, the relationship between LRG1 and spinal cord injury (SCI) has not been reported. The purpose of our study is to determine the predictive value of LRG1 for the prognosis of pediatric SCI (PSCI). Methods. This study recruited 64 patients with confirmed PSCI and 40 healthy controls at Foshan Traditional Chinese Medicine Hospital from January 2016 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Blood transcriptomic and metabolomic biomarkers have been proposed to be used in the identification of BRD cattle in feedlots ( Blakebrough-Hall et al, 2020 ; Sun et al, 2020 ). In this study, 101 DE genes were identified and the most informative marker LRG1 has been previously identified as a potential biomarker for different infections (e.g., active tuberculosis) in humans ( Wu et al, 2015 ; Fujimoto et al, 2020 ; Yang et al, 2020 ; Ma et al, 2021 ). We also found 31 metabolites were significantly associated with BRD infection, 13 of which were consistent with significant metabolites (e.g., citric acid, d -mannose, and acetic acid) identified by Blakebrough-Hall et al (2020) , even though the metabolite profiles used in the two studies were not exactly the same.…”
Section: Discussionmentioning
confidence: 99%
“…Blood transcriptomic and metabolomic biomarkers have been proposed to be used in the identification of BRD cattle in feedlots ( Blakebrough-Hall et al, 2020 ; Sun et al, 2020 ). In this study, 101 DE genes were identified and the most informative marker LRG1 has been previously identified as a potential biomarker for different infections (e.g., active tuberculosis) in humans ( Wu et al, 2015 ; Fujimoto et al, 2020 ; Yang et al, 2020 ; Ma et al, 2021 ). We also found 31 metabolites were significantly associated with BRD infection, 13 of which were consistent with significant metabolites (e.g., citric acid, d -mannose, and acetic acid) identified by Blakebrough-Hall et al (2020) , even though the metabolite profiles used in the two studies were not exactly the same.…”
Section: Discussionmentioning
confidence: 99%
“…There were relatively comprehensive clinical and basic studies on the function of LRG1 in stroke diseases. Serum level of LRG1 was identified as a potential indicator for the prediction of cardioembolic stroke, as well as pediatric spinal cord injury Ma et al, 2021). Apolipoprotein CII, LRG1, and C-reactive protein expression were significantly downregulated in poststroke depression relative to stroke subjects (Zhan et al, 2014).…”
Section: Part Five: Lrg1 Involved In Eye Diseasesmentioning
confidence: 99%
“…According to statistics, the annual cost of SCI in the United States is estimated to be between 5 million and 9 million US dollars, while in Australia, the figure is about 2 billion US dollars [ 5 7 ]. The pathogenic mechanism after SCI has not yet been fully elucidated, and the prognosis is poor, which affects the self-care ability of patients [ 8 ]. Therefore, finding prognostic markers for SCI and precise treatment are the top priorities.…”
Section: Introductionmentioning
confidence: 99%